Comparative Analysis of Reddit Posts and ChatGPT-Generated Texts’ Linguistic Features: A Short Report on Artificial Intelligence’s Imitative Capabilities - Arcenal, Erika Kristine E.; Capistrano, Licca Pauleen V.; De Guzman, Marielle Jessie D.; Forrosuelo, Micaela Isabel M.; Miranda, Janeson M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In recent years, the unprecedented explosion of artificial intelligence (AI), particularly generative AI, has dramatically and drastically altered many human fields, posing queries about how generative AI can imitate human language. Given the newness of generative AI as a controversial phenomenon, there is an urgency to closely examine how its linguistic outputs could mimic human language produced in natural contexts. Hence, in this short report, we discuss the observed similarities and differences in the linguistic features of the subreddit r/Marriage spouse appreciatory posts and ChatGPT-4 outputs. These results were the offshoot of our genre analysis on these two linguistic data sets. Our analysis revealed that ChatGPT-4 generated texts contain impeccable grammar, while the Reddit appreciatory posts have grammatical discrepancies, such as errors in subject-verb agreement, improper punctuation marks, and erroneous capitalization; ChatGPT-4 generated texts have more complex syntactical structure; Reddit dataset utilized more internet jargon, slang, and profanities and seems to be unpredictable and arbitrary in terms of textual length; and ChatGPT-4 outputs appear to overuse emojis while underuse emoticons and tend to use these digital linguistic elements without regard to their proper contexts. In light of these results, we claim that AI-generated texts, although they can mimic human language, this is on a mere surface level, and a closer inspection could uncover distinct variations. We recommend that future studies use more comprehensive and different datasets and continuously employ comparative and contrastive linguistic analysis to further investigate AI’s imitative capabilities.